Internal organizational communication and teamwork a health services managing entity - Troya Palomino, David (2024)
Internal organizational communication promotes the integration of people immersed in organizations, it also generates efficiency in the development of activities, in the same way it can help increase teamwork, which is essential for achieving objectives; This study was proposed as a general objective: to determine the relationship between internal organizational communication and teamwork in a health services administrative entity in northeastern Peru, with the participation of 162 workers, the methodology used for this study was For a basic, quantitative, descriptive-correlational and non-experimental design research, after processing the data, it was determined that p-value = 0.000, which indicates that there is a significant relationship between internal organizational communication and teamwork and the Rho Spearman coefficient = 0.556 indicates a considerable positive relationship. It was concluded that the actions carried out to improve internal organizational communication will proportionally impact the teamwork of the institution.